Asymmetric Hydrogenation Catalyzed by Bifunctional Knolker Type Complexes - Ferraccioli, Raffaella (Letters in Organic Chemistry, 2017)
Background: This review focuses on the recent advances in the asymmetric hydrogenation of pro-chiral C=O and C=N double bonds catalyzed by iron-catalysts based on chiral and achiral Knölker type complexes. Method: The bifunctional nature of such complexes made possible the development of two strategies to achieve asymmetric hydrogenation. The first approach is based on the design of chirally modified Fecomplexes, while the second one relies on the cooperative catalysis of an achiral iron-complex and a chiral additive. Forty-two papers are included in the review. Results: A number of chiral iron-complexes have been synthesized and characterized. Such catalysts have been applied in the direct and transfer hydrogenation of various ketones (up to 77% e.e.). Highly stereoselective hydrogenation of imines, benzoxazine and quinoxaline derivatives (up to 94% e.e.) was performed under H2 pressure by using a catalytic combination of the achiral Knölker’s complex and a chiral phosphoric acid which cooperatively act in determining enantioselectivity. Conclusion: The examples reported in the review highlight the great potential of Knölker type complexes in the field of asymmetric hydrogenation. Recent achievements can inspire the design of new catalysts capable of improving the transfer of chiral information to the substrate.
Keywords: Activated double bond